2016
DOI: 10.1071/bt15285
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy and germination in different populations of the Argentinan endemic halophyte grass, Sporobolus phleoides (Poaceae: Chloridoideae)

Abstract: Sporobolus phleoides Hack. is an endemic grass of Argentina that is considered an important genetic resource for saline environments. Knowledge of its germination behaviour is an indispensable requirement for the future potential use of this species. Thus, the effects of different factors on germination were evaluated in six representative populations collected from plants cultivated in a uniform environment. In addition, we investigated how the different parts of the seed contributed to dormancy and intraspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The way in which the seeds responded to the different treatments reveals the importance of seed covering for M. maximus germination. This is in agreement with previous studies that showed that in tropical grasses, like Panicum virgatum or Sporobolus phleoides, seed covering was responsible for germination inhibition (Duclos et al, 2014;Richard et al, 2016). The seed tissue enclosing the embryo plays a primary role in regulating germination and dormancy (Richard et al, 2016).…”
Section: Initial Seed Dormancy Testsupporting
confidence: 92%
See 1 more Smart Citation
“…The way in which the seeds responded to the different treatments reveals the importance of seed covering for M. maximus germination. This is in agreement with previous studies that showed that in tropical grasses, like Panicum virgatum or Sporobolus phleoides, seed covering was responsible for germination inhibition (Duclos et al, 2014;Richard et al, 2016). The seed tissue enclosing the embryo plays a primary role in regulating germination and dormancy (Richard et al, 2016).…”
Section: Initial Seed Dormancy Testsupporting
confidence: 92%
“…This rules out the effect of environmental factors on seed germination (Radosevich et al, 2007). Flower structures (lemma and palea) and seed covering were identified as major factors contributing to physical dormancy (Adkins et al, 2002;Richard et al, 2016). Megathyrsus maximus possesses dormant seeds (Smith, 1970;Martins and Silva, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…were stored dry at 20 • C for 0, 12, 18 and 24 months and then tested at 20, 30 and 30/20 • C, only seeds from two of the populations exhibited significant dormancy break. For the two populations with seed afterripening, however, maximum germination (after 12-18 months) was only 31% and 39% [125]. Further, in Asteraceae species with trimorphic diaspores, that is, three kinds of achenes in a capitulum that differ in size, mass and morphology, the amount of afterripening varies with the position of the achenes in the capitulum.…”
Section: Potential Problems With Afterripening Of Seedsmentioning
confidence: 88%
“…Temperature also plays a role in controlling seed dormancy (Offord & Meagher 2001), which is often interpreted as an adaptive response of a particular species to stress conditions (Garwood 1983;Mathias & Kisdi 2002), by means of increased adaptability and decreased germinability during an unfavorable time for seedling establishment (Keya 1997). Along with temperature, chemicals like KNO 3 have been revealed to be able to break seed dormancy, contributing to accelerate germination not only in grasses (Akamine 1944;Garber et al 1974;Eira 1983;Gazziero et al 1991;Frank & Nabinger 1996;Figueiredo et al 2012;Baličević et al 2016;Batista et al 2016;Kreuser et al 2016;Richard et al 2016;Libório et al 2017) but also in species from other plant groups (Wei et al 2010;Bian et al 2013;Cárdenas et al 2013;Lay et al 2015).…”
Section: Introductionmentioning
confidence: 99%